Avaliação da qualidade de vida do paciente transplantado hepático - Flor, Maria José Nascimento (2015)
The increased survival with liver transplantation sparked concern about the quality of life (QOL) of people in the short and long-term postoperative period. Objective: To evaluate the QOL of liver transplanted with donor graft, over the age of 60 years. Method: Prospective, descriptive and analytical, with a quantitative approach. Data were collected in Ceará Liver Transplant Center at Walter Cantídio University Hospital, and the participants were those undergoing liver transplantation in the period 2007 to 2013. It was used for data collection the Short Form-36 questionnaire ( SF-36), generic instrument to assess QOL; and to characterize the subjects, they used the form of call service and surgery of organ harvesting report. They were applied one hundred thirty-seven questionnaires by the researcher and four were answered by the patient, totaling 141 participants. The sample was divided into two groups: Group A (GA) consisting of receivers that received less donor liver grafts or equal to 60 years old, and Group B (GB) formed by receivers receiving liver graft donor above 60 years of age. Results: The mean age of the GA receptor was 52.5 (between 20 and 75 years) and GB was 54 (between 27 and 76 years); He was male in both groups; the domains of the SF-36: physical functioning, social aspect, mental health and role emotional, showed better score (p = 0.001) in the variable time of transplant, score MELD and recipient age in both groups, but no significant difference between they. Conclusion: The donor's age did not influence the quality of life of patients undergoing liver transplantation; the MELD score less than 21 had a positive influence on QOL in both groups; QOL in both groups was not modified after transplantation; post-transplant QOL was similar in the three groups divided by age. Keywords: Quality of Life. Liver transplant.